Digital Transformation of Land Governance: Implementing Electronic Land Administration Systems for Sustainable Land Administration – A Systematic Literature Review - Idris, Kamarul Akhtar; Hamzah, Abdul Halim (Journal of Technology Management and Business, 2026)
The rapid advancement of digital technologies has intensified the transformation of public sector governance, particularly in modernizing land administration systems that support sustainable land governance. However, many land administration institutions still operate through fragmented records, manual procedures and disconnected information systems, limiting transparency, operational efficiency and effective land information management. Within the context of digital transformation governance, Electronic Land Administration Systems (eLAS) have emerged as integrated digital platforms that combine land registry databases, cadastral records and geospatial information systems to enhance information system integration and digital service delivery. This study aims to examine the implementation of eLAS from a technology management perspective, focusing on technology adoption, institutional capability and governance readiness in digital land administration. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol using peer-reviewed publications retrieved from major databases including Scopus, Web of Science and IEEE Xplore. After applying defined inclusion criteria, 24 relevant studies published between 2022 and 2024 were analyzed using thematic analysis. The findings indicate that successful eLAS implementation depends on three interrelated factors: integrated land data management, supportive regulatory frameworks and strong institutional capability for managing digital transformation initiatives. Overall, the study highlights that effective digital transformation governance and strategic technology management are critical for advancing electronic land administration systems and achieving sustainable land administration.